Ovine Progressive Pneumonia: Diagnosis and Seroprevalence in the South of Sonora, Mexico - Mercedes Yannin Borquez Cuevas; Juan Francisco Hernández Chávez; Betsy Armenta Leyva; Jesús Raymundo Cedillo Cobián; Ramón Miguel Molina Barrios (Case Reports in Veterinary Medicine)
Ovine progressive pneumonia (OPP) is the most severe presentation of small ruminant lentivirus (SRLV) infection known as Maedi-Visna. Serological evidence in Mexico of the presence of this lentivirus was published in 1986. After that, studies revealed that SRLVs have a broad distribution in Mexico by detecting antibodies or/and molecular tests; however, a descriptive case of the disease has not been published. This work’s objective was to describe the diagnosis of a case of OPP through lesion description, serology, and molecular test. The histopathological study showed that lymph follicular hyperplasia, interstitial pneumonia, and smooth muscle hyperplasia were presented. The serological test demonstrated specific antibodies against the Maedi-Visna virus, and PCR analysis demonstrated a positive outcome. These results include the criteria for the diagnosis of OPP. The serological prevalence of this disease is presented, contributing to the knowledge of the ecology of this disease in the world. This work is the first case report of ovine progressive pneumonia in Mexico and evidence of seroprevalence in sheep herds from Sonora, Mexico.